Kemandirian Anak Berkebutuhan Khusus Melalui Pembelajaran Berdiferensiasi Program Sinau Ing Ndeso (SINDESO) di Sekolah Alam Pacitan - Aziza, Wahyu Nur; Tisngat, Urip; Pianto, Heru Arif (Ibtida'iy : Jurnal Prodi PGMI, 2025)
Abstract: This study aims to determine and describe the independence of Children with Special Needs (ABK) by implementing the Sinau Ing Ndeso program at Sekolah Alam Pacitan. The type of research was descriptive qualitative, using a single case study approach. Informants consisted of two assistant teachers and two students with special needs, selected using sampling techniques. Data collection used observation, interviews, and documentation. Qualitative data analysis used the Miles and Huberman concept through three activities, namely data reduction, data display, and conclusion drawing/verification. Based on the results of the data analysis, it was concluded that: 1) Sinau Ing Ndeso is a superior program carried out consistently every year in the second semester by Sekolah Alam Pacitan. The activities include, home industry, nature exploration, and learning with the community, 2) The implementation of the Sinau Ing Ndeso program has implications for the independence of students with special needs at Pacitan Nature School, the indicators are: initiative, self-confidence, ability to make decisions and progressive, 3) obstacles in the implementation of the Sinau Ing Ndeso program at Pacitan Nature School include two factors, namely obstacles from students (internal factors) and obstacles from other people or the environment (external factors). The barriers that become obstacles are the difficulties of children with special needs in activities to travel long distances and challenges in understanding the material, this is due to their physical and intellectual limitations, but there is support from teachers, parents, and the community as well as supporting facilities that will encourage students to be more enthusiastic and active in the Sinau Ing Ndeso program.